The effectiveness of positive psychotherapy on body image satisfaction and happiness in adolescent girls dissatisfied with body image - Bahari Sagalaksari, Seyedeh Fatemeh; Fakhri, Mohammadkazem; Haydari, Shaban (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the effectiveness of positive psychotherapy on body image satisfaction and happiness in adolescent girls dissatisfied with body image. Methods: The present study was a quasi-experimental design with pre-test-post-test and follow-up design. Among the adolescent girls who were dissatisfied with the body image, a sample of 30 people was selected by purposive non-random sampling method and was randomly replaced in two groups of experimental (positive psychotherapy) and control. (15 people in each group). After evaluation, 30 adolescent girls who were dissatisfied with the body image, who scored lower than the cut score of the image satisfaction questionnaire and had the necessary conditions, were identified and then divided into two groups of 15, one experimental group and one control group. Then, 8 sessions of 90-minute positive psychotherapy of Seligman (2008) in the experimental group were performed in person and in accordance with health protocols. Data were collected using Happiness Questionnaire and Image Satisfaction Scale. Data were analyzed using repeated measures analysis of variance with SPSS-22 software. Results: The results showed that in the post-test and follow-up stages, positive psychotherapy was effective on body image satisfaction (F=49.86, P<0.001) and happiness (F=13.53, P<0.001). And in the post-test and follow-up stages, treatment based on acceptance and commitment were effective on body image satisfaction and happiness, and in other cases no significant difference was observed. Conclusion: In general, according to the results of the study, it is possible to use positive psychotherapy and therapy based on acceptance and commitment to improve the psychological problems of adolescent girls.